Strategi Teknis Untuk Mengatasi Tekanan Berlebih Dalam Sistem Distribusi Air Bersih Di Daerah Pegunungan - Pureza Marenshaputri; Rizka Indri Meutia; Mohamad Yudi Purnawan (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
In gravity-based water distribution systems in mountainous regions, excessive hydrostatic pressure—caused by significant elevation differences can lead to pipeline stress, leakage, or even bursts. To control this, pressure-reducing valves (PRVs), break-pressure tanks, or energy recovery systems like micro-hydropower turbines are strategically installed at key elevation drops. These methods ensure pressure stability, protect infrastructure, and can also enhance system efficiency and sustainability when excess pressure is harnessed for energy generation. This study examines technical strategies for controlling excessive hydrostatic pressure in gravity-based water distribution systems in mountainous regions, with a focus on the Cilongkrang system in Majalengka, Indonesia. With an elevation difference of over 950 meters between the spring and service zone, the system faces potential hydrostatic pressure exceeding 90 bar, far beyond the design limits of standard pipelines. The research compares two pressure control technologies Pressure Reducing Valves (PRV), and Break Pressure Tanks (BPT). By evaluating their hydraulic performance, operational practicality, lifecycle costs, and field applicability. The analysis utilizes topographic data, pressure modelling, and actual project cost estimates to quantify the effectiveness of each option. Results show that BPTs are more cost-effective and reliable for large elevation drops in rural areas with sufficient land, while PRVs are suitable for confined, urban installations requiring precision. This study contributes a practical framework for designing sustainable gravity-fed water supply systems in extreme topographic conditions.